Laboratory diagnosis of persistent human chlamydial infection - Puolakkainen, Mirja (Frontiers in Cellular and Infection Microbiology, 2013)
Diagnostic assays for persistent chlamydial infection are much needed to conduct high-quality, large-scale studies investigating the persistent state in vivo, its disease associations and the response to therapy. Yet in most studies the distinction between acute and persistent infection is based on the interpretation of the data obtained by the assays developed to diagnose acute infections or on complex assays available for research only and/or difficult to establish for clinical use. Novel biomarkers for detection of persistent chlamydial infection are urgently needed. Chlamydial whole genome proteome arrays are now available and they can identify chlamydial antigens that are differentially expressed between acute infection and persistent infection. Utilizing these data will lead to the development of novel diagnostic assays. Carefully selected specimens from well-studied patient populations are clearly needed in the process of translating the proteomic data into assays useful for clinical practice. Before such antigens are identified and validated assays become available, we face a challenge of deciding whether the persistent infection truly induced appearance of the proposed marker or do we just base our diagnosis of persistent infection on the presence of the suggested markers. Consequently, we must bear this in mind when interpreting the available data.